IMPLEMENTATION OF THE 2013 CURRICULUM IN TEACHING WRITING EXPLANATORY TEXTS USING CONCEPT MAPS IN INDONESIAN LANGUAGE LEARNING AT JUNIOR HIGH SCHOOL - Hermaditoyo, Stanislaus; I Nyoman Sudiana; Ida Bagus Putrayasa; Ni Made Rai Wisudariana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The 2013 curriculum in Indonesian language education explains learning based on texts. It can be said that the 2013 curriculum relies on texts, which is why it is referred to as a text-based curriculum. An explanatory text is a written explanation related to natural phenomena, social, cultural issues, and so on. Based on the journal that has been analyzed, the researcher found that students have not fully understood the structure and linguistic elements of explanatory texts and there is a lack of teaching methods that can stimulate ideas and creativity in writing explanatory texts. Therefore, in this study, the author introduces the concept map method as one of the methods that can overcome students' difficulties in writing explanatory texts. The aim of this research is to emphasize the implementation of the 2013 Curriculum in Teaching Explanatory Text Writing Using Concept Maps in Indonesian Language Learning at Junior High School. The method applied in this study is library research. The research data was obtained from articles sourced from journals. The results of the study show that from various journals that have been analyzed, it has been proven that the concept map method can help students fully understand the structure and linguistic elements in writing explanatory texts. With the concept map method, students are able to write an explanatory text. The concept map serves as an effective method in the learning process, thereby improving student knowledge in writing explanatory texts.